Shelf Life Estimation of Gotu Kola Leaf (Centella Asiatica L. Urban) Chips on Polypropylene Plastic Packaging During Storage using ASLT Method (Accelerated Shelf Life Testing) Arrhenius Model - Satyajaya, Wisnu; Lestari, Puput; Indraningtyas, Lathifa; Astuti, Sussi (Journal of Tropical Agricultural Engineering and Biosystems - Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2024)
Gotu cola leaf chips produced by the Women Farmers Group in the city of Pagar Alam, South Sumatra are packaged using polypropylene plastic packaging and the shelf life is not yet known, so a test  is needed to estimate the shelf life of the gotu kola leaf chips produced by KWT.  This research aims to determine the shelf life of gotu kola leaf chips in polypropylene packaging using the Arrhenius model ASLT (Accelerated Shelf Life Test). The study was structured descriptively with two replications. The chips made from gotu kola leaves were stored at temperatures of 30 C, 35 C, and 40 °C in polypropylene (PP) packaging.with a thickness of 0.08 mm for one month (28 days). Observations were made on the parameters of water content, free fatty acid levels, and sensory (color, aroma, and texture of gotu kola leaf chips) once a week, namely on days 0, 7, 14, 21, and 28.  Determined the shelf life of gotu kola leaf chips using the ASLT model with Microsoft Excel 2010 software. The results showed that gotu kola leaf chips in polypropylene packaging at 30 °C had a shelf life of 76.67 days (2.57 months) on the zero order of the Arrhenius model ASLT method.